Agenda web use for the development of vocabulary acquisition skills in fifth graders at Aguacatal School, 2016 - Martínez, Hellen (David, Panamá : UDELAS, 2016)
This work is focused in the idea tha there is the need to inform teachers about an important and available resource that the technological web provides, and also to provide the suggestions of the way to use if from the base of the skill that it is directed to and the signifacnt amount of activities that are available to teach English with these types of technological tools.
TABLE OF CONTENTS GRAPHIC INDEX INTRODUCTION CHAPTER I: AGENDA WEB IMPACT FOR THE DEVELOPMENT VOABULARY ACQUISITION SKILLS CHAPTER II: THEORICAL FRAMEWORK 2.1. Agenda web 2.1.1. Characteristics of Agenda Web 2.1.2. Direct languaje skills developed by Agenda Web 2.1.3. Indirect competency and skills developed by Agenda Web 2.2. Theoretical support of the use of ICT (Information and Communication Technology) into Education 2.2.1. The society of knowledge and socia media 2.2.2. Value added of ICT (Information and Communicat6ion Technology) 2.3. Students that society needs 2.4. Teacher´s role in the use of ICT 2.5. Student's role in the use of ICT 2.6. Telematics and globalización of knowledge 2.7. Impact of ESL (English as Second Language) or EFL (english as Foreing Language) website into the learnign of vocabulary CHAPTER III: METHODOLOGICAL FRAMEWORK CONCLUSIONS REFERENCES
Incluye Table of Contents
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; VOCABULARY -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN ESPECIAL Y PEDAGÓGICA; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; AGUACATAL SCHOOL - CHIRIQUÍ PANAMÁ